Improvement in Quality Metrics Outcomes and Patient and Family Satisfaction in a Neurosciences Intensive Care Unit after Creation of a Dedicated Neurocritical Care Team - Yaw Sarpong; Premkumar Nattanmai; Ginger Schelp; Robert Bell; Keerthivaas Premkumar; Erin Stapleton; Ashley McCormick; Christopher R. Newey (Critical Care Research and Practice)
Introduction. Dedicated neurointensivists have been shown to improve outcome measurements in the neurosciences intensive care unit (NSICU). Quality outcome data in relation to patient and family satisfaction is lacking. This study evaluated the impact of newly appointed neurointensivists and creation of a neurocritical care team on quality outcome measures including patient satisfaction in a NSICU. Methods. This is a retrospective study of data over 36 months from a 14-bed NSICU evaluating quality outcome measures and anonymous patient satisfaction questionnaires before and after neurointensivists appointment. Results. After appointment of neurointensivists, patient acuity of the NSICU increased by 33.4% while LOS decreased by 3.5%. There was a decrease in neurosciences mortality (35.8%), catheter-associated urinary tract infection (50%), central line associated bloodstream infection (100%), and ventilator-associated pneumonia (50%). During the same time, patient satisfaction increased by 28.3% on physicians/nurses consistency (p=0.025), by 69.5% in confidence/trust in physicians (p<0.0001), by 78.3% on physicians treated me with courtesy/respect (p<0.0001), and by 46.4% on physicians’ attentiveness (p<0.0001). Ultimately, patients recommending the hospital to others increased by 67.5% (p<0.0001). Conclusion. Dedicated neurointensivists and the subsequent development of a neurocritical care team positively impacted quality outcome metrics, particularly significantly improving patient satisfaction.